Access to Justice for Victims of Dating Violence: Gender Perspective - Trianah Sofiani (Sawwa: Jurnal Studi Gender, 2021)
Legal handling of violence against women, including dating violence, ideally fulfills three elements of the legal system, namely legal structure, legal substance, and legal culture. However, in its implementation, the legal handling of violence during dating is still gender biased. This article is the result of qualitative research with a gender perspective that explores the forms, causes, impacts of dating violence and access to justice for the victims of dating violence at Islamic Universities in Pekalongan. Data collection used observation, interviews, questionnaires, and literary studies and they were analyzed through an interactive model. The results showed the shape of dating violence, i.e.: verbal-emotional, physical, sexual, and economic. The main causes of dating violence are patriarchal culture and a lack of understanding of gender, which causes gender inequality, gender-biased parenting, women stereotype, and the absence of regulation about dating violence. Dating violence affects not only victims but also the perpetrators. The dating violence victims have not gained access to justice, because the legal system, which includes the substance, structure, and legal culture is still gender biased and patriarchal. This condition is confirmed by the fact that the community and victims do not know, understand, and be aware of their rights to justice. Therefore, we need efforts to understand gender and dating violence, including access to justice for victims, through student activity in and out of campus. Lawmaking about eliminating dating violence in the future (ius constituendum) must be part of the political agenda of the government and legislative.